Studi Fenomenologi: Perbedaan Perspektif Job Hopping Pada Karyawan Wanita Dan Pria - Kamelia Kamelia; Edy Purwanto (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2025)
Background – The phenomenon of job hopping, defined as frequently changing jobs within a short period, is becoming increasingly common in Indonesia. Various factors drive this behavior, ranging from skill enhancement to better career opportunities. This study aims to understand the underlying reasons behind the decision to change jobs, as well as whether there are differences in perspectives between men and women regarding the reasons for job hopping. Purpose – This study aims to investigate whether there are differences in the factors motivating employees to engage in job hopping rapid job changes from one company to another between women and men. Design / Methodology / Approach – A phenomenological approach was used to explore the subjective experiences of participants. Data were collected through in-depth interviews with 10 employees experienced in job hopping, providing valuable perspectives. Findings – Both male and female employees share similar work motivations based on McClelland’s three needs theory: achievement, affiliation, and power. They are motivated to meet targets, build positive relationships, and attain better positions. The main reasons for job hopping include desires for higher salary, career development, alignment of personal values with the organization, and work-life balance. Despite differences in context and experiences, work motivation and the desire to change jobs are not significantly influenced by gender. The study also reveals the role of Indonesian culture in shaping work decisions, such as men’s role as breadwinners and women’s family priorities. Conclusion – There is no significant difference in motivation and intention to job hop between men and women. Gender is not a dominant factor; rather, job hopping decisions are influenced more by work situations, personal values, and sociocultural factors. These findings contrast with some previous studies that reported gender differences and highlight the importance of considering local context in understanding employee career dynamics. Research Implications – The findings can assist HR management in developing more personalized and equitable retention strategies, such as open communication, a supportive work environment, and career paths tailored to gender characteristics. Limitations – This study involved only ten informants and is qualitative in nature, thus it does not represent a broader population and the results are subjective.